(untitled) (Indian Journal of Animal Production and Management, 2016)
Changes in living organisms’ internal environment are generally expressed by behavioural signs, which reflect the health status of animals and considered as true indicator of illness. In traditional animal husbandry system, the simple way to recognize the illness in animals only when they become depressed or off fed. Changes of feeding, drinking/suckling, lying, standing, social and rumination behaviour can be helpful for early prediction or identification of abnormal health in dairy cattle. Tail raising, pawing, restlessness, looking back to abdomen, hunching of back, rubbing against wall and urination behaviour can predict the incidence of dystocia in dairy cows. In addition, walking/stepping, turning head against udder and self grooming behaviour also alter in cows and can be helpful for early prediction or identification of abnormal health. Validation of disease specific behavioural risk factors using automatic electronic monitoring system in a particular farm with defined housing design and management practices can improve the accuracy of prediction or identification of cows that are going to develop ill health. Therefore, managemental interventions at proper time based on behaviour change can be utilized as effective means to reduce the subsequent abnormal health in dairy cattle.